Evaluating Translation AI’s Effectiveness in Enhancing English Vocabulary Acquisition Among University Students: A Global Communication Perspective - Fakira, Jakiatul; Ilham, Ilham; Hidayati, Hidayati; Bafadal, Moh Fauzi (Universitas Pahlawan Tuanku Tambusai, 2025)
The rapid advancement of AI-driven translation tools has significantly transformed English vocabulary acquisition, particularly in global communication. These tools offer innovative methods for enhancing language learning by providing instant translations, contextual examples, and user-friendly interfaces. However, despite their widespread adoption, the effectiveness of these tools in improving vocabulary acquisition remains underexplored. This study investigates the role of AI translation tools in facilitating vocabulary development among university students. By employing a mixed-method approach that combines quantitative analysis with qualitative insights, the research evaluates the impact of these tools on learners’ vocabulary retention and usage. The findings reveal that AI translation tools can effectively support vocabulary learning by offering immediate feedback and diverse contextual applications. However, challenges such as over-reliance on technology and inaccuracies in translation highlight the need for cautious implementation. The study concludes that AI-driven translation tools have the potential to enhance vocabulary acquisition and foster intercultural communication, provided they are integrated thoughtfully into educational practices. Further research is recommended to explore their long-term effects and optimize their role in language education.